1993
DOI: 10.1302/0301-620x.75b1.8421010
|View full text |Cite
|
Sign up to set email alerts
|

Vascularity of the humeral head after proximal humeral fractures. An anatomical cadaver study

Abstract: We studied the arterial anatomy and the effect of fourpart fractures on the vascularity of the humeral head, using barium sulphate perfusion of 16 cadaver shoulders. The main arterial supply to the humeral head was via the ascending branch of the anterior humeral circumflex artery and its intraosseous continuation, the arcuate artery. There were significant intraosseous anastomoses between the arcuate artery and: 1) the posterior humeral circumflex artery through vessels entering the posteromedial aspect of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
104
1
10

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(127 citation statements)
references
References 0 publications
7
104
1
10
Order By: Relevance
“…There is a high risk of osteonecrosis because of damages to the vascular supply of the dislocated head fragment [1,2]. In accordance with the literature, we found poor results for four-part fractures treated without osteosynthesis.…”
Section: Discussionsupporting
confidence: 88%
“…There is a high risk of osteonecrosis because of damages to the vascular supply of the dislocated head fragment [1,2]. In accordance with the literature, we found poor results for four-part fractures treated without osteosynthesis.…”
Section: Discussionsupporting
confidence: 88%
“…The artery gives off one principal branch, the arcuate artery, which ascends on the lateral border of the groove and enters the proximal humerus at the level of the greater tuberosity [9]. Previous studies have shown that this artery is the dominant blood supply to the humeral head [2].…”
Section: Discussionmentioning
confidence: 99%
“…1 The location where extreme care should be taken to protect the anterior humeral circumflex artery (point 1). Point 2 shows the prominence of the lesser tuberosity Injury to this artery, along with the axillary nerve, is common during surgical procedures to the shoulder and poses a risk to the rich network of anastomoses in the posteromedial humeral epiphysis [6,7,9]. Therefore, the objective of this study was to investigate the anatomy of these structures to improve understanding of "safe zones" during operations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,25 On the other hand, new progress in PHF studies, especially in vascularization, allows the definition of important new characteristics for treatment decision-making. [26][27][28][29][30] Because important new concepts for prognosis and treatment of PHF do not easily fit in past classification systems, some authors have proposed new imaging techniques 8,12 or new functional classifications. 14 Since 2003, new systems of fracture classifications have been published.…”
Section: Background On the Diagnosis And Classification Of Phfmentioning
confidence: 99%